Dental Management of a Young Child Affected by Galactosialidosis and a Gigantic Abdominal Growth - Yoselín Méndez-Salado; Paola De Ávila-Rojas; Amaury Pozos-Guillén; Raúl Márquez-Preciado; Miguel Ángel Noyola-Frías; Socorro Ruiz-Rodríguez; Arturo Garrocho-Rangel (Case Reports in Dentistry)
Galactosialidosis (GS) is a rare form of lysosomal storage disease that involves a broad spectrum of skeletal and soft tissue abnormalities. We report here on a 4-year 7-month-old boy with mild mental retardation, exhibiting multiple caries cavities and associated infectious foci and macroglossia. A huge abdominal enlargement due to peritoneal ascites was evident. Behavioral management and patient positioning on the dental chair represented a true challenge. The patient was treated under general anesthesia. However, life-threatening postoperative complications occurred because of the impossibility of extubating the patient. A very careful preanesthetic assessment is crucial in children affected by general conditions associated with airway anomalies, such as GS.